Simulations can improve nursing education in general, especially in psychiatric simulation and critical care - Kokol, Peter (Evidence-based nursing, 2023)
Implications for practice and research Simulation-based nursing education can enhance nursing education and increase the competence level of practising nurses, which in turn can improve their job satisfaction and, consequently, patient safety and well-being. The cluster analysis identified five hot topics: interprofessional simulation in patient care teams, patient simulation in psychiatric nursing education, virtual reality simulation in midwifery and nursing education, simulation in critical care nurses’ continuing education/training and simulation in paediatric resuscitation education. A different kind of knowledge synthesis study, namely, a systematic review, comes to comparable results regarding virtual reality simulations as an effective pedagogy approach in nursing education.5 A recent meta-analysis and metaregression-based systematic review showed that SBNE, compared with conventional educational strategies, might be a more effective strategy for reducing anxiety and increasing self-confidence among nursing students.6 The importance of this study is to show that based on the increased research literature production and new opportunities offered by technological advances in virtual and augmented reality platforms, SBNE is one of the key research priorities in nursing education.